2022
DOI: 10.1002/cam4.4898
|View full text |Cite
|
Sign up to set email alerts
|

A novel pyroptosis risk model composed of NLRP6 effectively predicts the prognosis of hepatocellular carcinoma patients

Abstract: Background Pyroptosis is a unique inflammatory‐related cell death process, and inflammation is considered to be a key factor in hepatocellular carcinoma (HCC). However, the pyroptosis landscape in HCC has not been thoroughly studied. Methods Clinical data and RNA sequencing data of HCC patients were collected from The Cancer Genome Atlas database, and differentially expressed genes (DEGs) associated with pyroptosis were discovered. The relationship between DEGs and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…NLRP6, a novel member of the nucleotide binding domain and leucine-rich repeat-containing (NLR) family, shows abundant expression in the liver and intestine and plays an essential role in regulating inflammation and shaping intestine microbiota [ 58 ]. It is demonstrated that NLRP6 drives the progression of liver diseases by causing dysbiosis of the intestine, and its expression level is strongly related to the prognosis of HCC by regulating the progress of pyroptosis [ 59 , 60 ]. GRM8 modulates glutamatergic and gamma-aminobutyric acid (GABA) neurotransmission, and HTR5A belongs to the 5-HT receptor family and is deeply involved in regulating the nervous system [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…NLRP6, a novel member of the nucleotide binding domain and leucine-rich repeat-containing (NLR) family, shows abundant expression in the liver and intestine and plays an essential role in regulating inflammation and shaping intestine microbiota [ 58 ]. It is demonstrated that NLRP6 drives the progression of liver diseases by causing dysbiosis of the intestine, and its expression level is strongly related to the prognosis of HCC by regulating the progress of pyroptosis [ 59 , 60 ]. GRM8 modulates glutamatergic and gamma-aminobutyric acid (GABA) neurotransmission, and HTR5A belongs to the 5-HT receptor family and is deeply involved in regulating the nervous system [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, compared to traditional TNM stage and other published prediction models [ 20 23 , 34 ], we developed a 16-gene prognostic model with a better and more robust predictive accuracy (most of AUC value > 0.8). These sixteen genes collectively contribute to HCC biology by either promoting cancer development or inhibiting tumor growth, depending on their specific functions.…”
Section: Discussionmentioning
confidence: 99%
“…The correlations between RGPRG score and clinical characteristics were further estimated using the Wilcoxon rank sum test. Decision curve analysis (DCA) was used to evaluate and compare multiple published clinical prediction models [ 20 23 ]. None and ALL are two reference lines, and the closer the curves of other models are to these two lines, the less clinical utility they have.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, further experimental research on the inflammasome and pyroptosis in relation to intestinal microbiota and the gut–liver axis is required. As a potential key molecule in the gut–liver axis, NLRP6 is not only highly expressed in intestinal epithelial cells ( 45 ) but also specifically expressed in liver parenchymal cells ( 195 ). In alcoholic liver disease, the gut microbiota and its components, including LPS and dsDNA ( 196 ), activate the TLR4/MyD88–ROS pathway in the portal circulation, thereby triggering NLRP6 inflammasome-mediated pyroptosis ( 196 ).…”
Section: Discussionmentioning
confidence: 99%
“…NLRP6 is a protective factor against the development of nonalcoholic fatty liver disease (NAFLD) and has been found to play a crucial role in inflammatory and immunological responses ( 44 ). Reports have suggested that the NLPR6 gene is a candidate tumor suppressor gene ( 45 ). This gene has been shown to be capable of inducing pyroptosis in hepatocellular carcinoma and is linked to higher levels of immune cell infiltration, both of which are associated with a more favorable prognosis.…”
Section: Composition and Classification Of Inflammasomesmentioning
confidence: 99%